Pengabdian Metode Sorogan dalam Pembelajaran Al-Qur’an di Madrasah Diniyah Awwaliyah Ar-Rahman Ngrogung - Khoirul Ikwan; Moh. Hazim Ahrori (Social Science Academic, 2025)
The sorogan method is one of the methods of learning the Qur'an that has been widely used in Madrasah Diniyah. This method is done by students reading the Qur'an in front of the teacher, then the teacher provides correction and guidance directly. This study aims to find out how the sorogan method is applied in learning the Qur'an and to find out the effectiveness of the sorogan method in improving students' ability to read the Qur'an. This study uses a qualitative approach, which contains data citations to provide an overview of the presentation of the report. This research was conducted at Madrasah Diniyah Awwaliyah Ar-Rahman Jati Ngrogung. The subjects of this study are school principals, teachers and students. The data collection techniques in this study are interviews, observations and documentation. The result of this research is that the process of applying this sorogan method is divided into 3, namely: beginning, core and end. The application of this sorogan method is applied to students who have just entered the madin school until they reach the goal of the madin itself, which is to be able to read the Qur'an fluently. Supporting factors in the application of this sorogan method include: adequate madrasah facilities and repetition in the material. Meanwhile, the bland factors are: students do not want to reread the Qur'an and lack of application of tajweed in the sorogan process.